Problematizing and politicizing smart city-regions: Is devolution smart? - Calzada, I (FrancoAngeli, 2018)
This paper problematizes the meanings, governance implications, and techno-political shortcomings of so-called ‘smart cities’ through pervasive transitions taking place in Europe by presenting a six-dimensional conceptual framework to politicize ‘smart city-regions’ as complex, transcalar, data-driven, multi-stakeholder-focused, experimental, and, supposedly, democratic techno-territorial assemblages. The momentum for smart city-regions is particularly relevant given an increasing number of ongoing reforms of administrative borders and competences of local governments fuelled by devolution in countries such as the UK, Spain, and Italy. Hence, by blending governance with technological and territorial issues, this paper elucidates that devolution should be addressed in the implementation of smart strategies stemming from (i) transcalar overlaps and contradictions; (ii) data literacy, ownership, and management; (iii) multi-stakeholder complex urbanity; and (iv) democratic and digital citizenship. The paper applies this framework to four cases: Bristol and Glasgow (UK) and Barcelona and Bilbao (Spain).